Community Empowerment Produces Virgin Coconut Oil (VCO) and Vatarana Utilizing Automatic Flash Oil Technology - Husaini, Husaini; Italina, Cut; Handayani, Sri; Makawiyah, Makawiyah; Mirna, Mirna; Alfairus, Nanda (Pascasarjana Universitas Mataram, 2024)
This Community Service Program implements a technology-based empowerment model for optimizing Virgin Coconut Oil (VCO) and Vatarana production in Pidie Regency, Aceh. Utilizing a mixed-method approach with sequential explanatory design, the program was conducted over 12 months (2023-2024) involving 32 members from two business groups. Technological intervention was carried out through the implementation of an Automatic Flash Oil system that integrates automation with cold extraction principles. Results showed significant improvements in: (1) production efficiency (47.3%, p<0.01) with process time reduction from 168 hours to 36 hours per batch; (2) product quality meeting SNI 7381:2008 standards across all parameters; (3) increased business income (35.2%, p<0.01); and (4) marketing network expansion to 12 provinces. Multivariate analysis indicated a strong correlation (r=0.78) between technology adoption and income improvement. This program contributes to the development of a replicable technology-based SME empowerment model, with an 85% sustainability rate after 6 months of implementation.